The Relevance of Behavioral Counseling with Positive Reinforcement Techniques to Improve Students' Self-Confidence - Sutraptawan, Dewa Ngakan Nyoman (International Journal of Multidisciplinary Sciences, 2024)
Confidence is an important aspect of human life and can be categorized into one of the non-cognitive aspects. Even though it sounds simple, in reality, self-confidence often neglects its role in human life. In essence, people who have intellectual intelligence when supported by good self-confidence will produce an interaction within themselves, especially in the social field. The purpose of this study is to describe and interpret the relevance between the application of behavioral counseling and positive reinforcement techniques in increasing students' self-confidence. The approach used in this study was counseling guidance action research which emphasized the application of behavioral counseling. The target of the improvement process in this study was students’ self-confidence through the application of behavioral counseling. The main subjects used in this study were students in grade XI in the MIPA specialization program at SMA Negeri 1 Susut in the academic year 2022/2023 who had low self-confidence. This research was conducted at SMAN 1 Susut. The sample of this study was students in class XI MIPA 3 in the academic year 2022/2023 that consist of 16 males and 13 females for a total of 29 students. In increasing students' self-confidence, the relevance of applying Behavioral Counseling with positive reinforcement techniques is felt to be very effective. This can be seen in the results of thedata analysis and discussion of research results. It can be stated that in cycle I (first) there was an increase in students' self-confidence of 46.64 %. In the action cycle II (second) there was an increase of 70.75%. The results of the research showed that the self-confidence of students in class XI MIPA 3 SMA Negeri 1 Susut in the academic year 2022/2023. Therefore, the results of this study show there is great influence of the relevance of behavioral counseling with positive reinforcement techniques in improving students’ self-confidence in class XI MIPA 3 SMA Negeri 1 SUSUT in the academic year 2022/2023.